The Mayer-Eymar collection of Cenozoic mollusks - Walter Etter (Swiss Journal of Palaeontology, 2022)
Abstract Karl Mayer (later Karl Mayer-Eymar, 1826–1906) was a stratigrapher and palaeontologist who assembled during his long career a collection of Cenozoic (then “Tertiary”) mollusks that numbers more than 500′000 specimens. He mostly collected them himself at various localities in Europe and Egypt. In more than 175 publications he described more than 1100 new bivalve and gastropod species, the types of which are of paramount importance for mollusk taxonomists. Based on his collection, he furthermore, erected 13 new Cenozoic stages, five of them still in use today. Here the structure and content of this collection is described, along with an explanation of the labels which are at first not so easy to understand. The Mayer-Eymar collection is in the propriety of the “Eidgenössische Technische Hochschule” (ETH) in Zürich. From 1966 until 2020 it was on a permanent loan to the Natural History Museum Basel, where it was also curated. In October 2020 the collection was returned to the ETH.